Effect of number and timing of pinching on reproductive growth of potted poinsettia (Euphorbia pulcherrima Willd.) - Lee Abdullah, Thohirah; Ong, Jyh Seng (Universiti Putra Malaysia Press, 2003)
An experiment to evaluate effects of pinching number (unpinched, once-and twice-pinched) and timing (early- and late-pinched) on reproductive growth of poinsettia was conducted. The results showed that late-pinched plants were delayed in floral induction, bract colour development and finish date compared to early-pinched plants. However, the time of pinching did not significantly affect the number of bracts and bract area, once- and twice-pinched treatment delayed floral induction, bract colour development and finish dates compared to unpinched plants. The number of bracts and bract area were increased after the plants had been pinched once or twice.